STUDI KESESUAIAN LAHAN TAMBAK DI KAWASAN BEKAS PELABUHAN BATUBARA KECAMATAN SATUI KALIMANTAN SELATAN DENGAN SISTEM INFORMASI GEOGRAFIS - Yuliyanto Yuliyanto (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
Satui district is the largest coal producing area in South Kalimantan and it has a coastal and marine areas that quite broad. Mining activity causes a lot of impact of environmental pollution, especially water pollution. Conditions of aquaculture in Satui district is currently vulnerable to damage resulting from the former coal mining and the construction of the illegal construction of the specific port. The purpose of this study is collecting the parameters of land suitability evaluation for pond in the Satui district pond and knowing the level of suitability coastal ponds in the Satui district with GIS. The method that applied at this research are observing and analyzingthe criteria parameters of environmental quality for pond development which supported by fielddata to find the level of compliance. This study including some stages, they areimage using, field data collection and data analysis. Water quality, soil and landsuitability analysis, the paramaters study at this study are slope, the zone fisiology,soil texture and water supply. Based on GIS analysis, the area very suitable for pond around the port is 486 ha, the suitable area is 406 ha, the moderate area is 1.734 ha and unsuitable area is 1.197 ha.